Hydrothermal Synthesis and Characterization of PEG-Mn3O4 Nanocomposite - Karaoğlu, E.; Deligöz, H.; Sözeri, H.; Baykal, A.; Toprak, M. S. (Nano-Micro Letters, 2011)
Here, we report on the synthesis of PEG-Mn3O4 nanocomposite (NP’s) via a hydrothermal route by using Mn(acac)2, ethanol, NH3 and PEG-400. The crystalline phase was identified as Mn3O4. The crystallite size of the PEG-Mn3O4 nanocomposite was calculated as 12±5 nm from X-ray line profile fitting and the average particle size from TEM was obtained as 200 nm. This reveals polycrystalline character of Mn3O4 NP’s. The interaction between PEG-400 and the Mn3O4 NP’s was investigated by FTIR. Temperature independent AC conductivity of PEG-Mn3O4 nanocomposite beyond 20 kHz provides a strong evidence of ionic conduction through the structure. The conductivity and permittivity measurements strongly depend on the secondary thermal transition of nanocomposite beyond 100°C. Above that temperature, Mn3O4 particles may interact with each other yielding a percolated path that will facilitate the conduction. On the other hand, the relatively lower activation energy (Ea=0.172 eV) for relaxation process suggests that polymer segmental motions of PEG and electrons hopping between Mn2+ and Mn3+ may be coupled in the sample below 100°C. Room temperature magnetization curve of the sample does not reach to a saturation, which indicates the superparamagnetic character of the particles. As the temperature increases, the frequency at which (ε″) reaches a maximum shifted towards higher frequencies. The maximum peak was observed at 1.4 kHz for 20°C while the maximum was detected at 23.2 kHz for 90°C.